Insect-mediated apparent competition between mammals in a boreal food web - Labadie, Guillemette; Fortin, Daniel; McLoughlin, Philip D.; Hebblewhite, Mark (Proceedings of the National Academy of Sciences, 2021)
While the important role of animal-mediated interactions in the top-down restructuring of plant communities is well documented, less is known of their ensuing repercussions at higher trophic levels. We demonstrate how typically decoupled ecological interactions may become intertwined such that the impact of an insect pest on forest structure and composition alters predator–prey interactions among large mammals. Specifically, we show how irruptions in a common, cyclic insect pest of the boreal forest, the spruce budworm (Choristoneura fumiferana), modulated an indirect trophic interaction by initiating a flush in deciduous vegetation that benefited moose (Alces alces), in turn strengthening apparent competition between moose and threatened boreal caribou (Rangifer tarandus caribou) via wolf (Canis lupus) predation. Critically, predation on caribou postoutbreak was exacerbated by human activity (salvage logging). We believe our observations of significant, large-scale reverberating consumer–producer–consumer interactions are likely to be common in nature.